Epistemological Foundations of Islamic Education: Bayani, Burhani, and Irfani - Aulia Rizki; Syamsul Rijal (Al-Mudarris, 2026)
This study examines the epistemological foundations of Islamic education through the integrative analysis of three major epistemologies in the Islamic intellectual tradition: bayani, burhani, and ‘irfani. While discussions of these epistemologies are often situated within philosophical discourse, this article positions them explicitly within the framework of Islamic educational theory. Using a qualitative library research method, the study critically analyzes classical and contemporary sources to explore how each epistemology contributes to the construction of educational orientation, curriculum design, and teaching–learning processes. The findings indicate that bayani epistemology provides a textual-normative foundation that shapes value-based curriculum content and ethical guidance in education. Burhani epistemology strengthens critical thinking, systematic reasoning, and intellectual rigor within pedagogical practice. Meanwhile, ‘irfani epistemology emphasizes character formation, spiritual development, and the cultivation of inner awareness as integral dimensions of learning. Rather than functioning in isolation, these epistemologies offer complementary educational paradigms that collectively support a holistic model of Islamic education. This study contributes to the development of Islamic educational philosophy by proposing an integrated epistemological framework that bridges revelation, reason, and spirituality. Such integration is essential for constructing an educational paradigm that is intellectually sound, spiritually grounded, and responsive to contemporary challenges.